2009
DOI: 10.1038/hr.2009.175
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of aliskiren in Japanese hypertensive patients with renal dysfunction

Abstract: This 12-week, multicenter, open-label study assessed the efficacy, pharmacokinetics and safety of a once-daily aliskiren in Japanese hypertensive patients with renal dysfunction. Patients (n¼40, aged 20-80 years) with mean sitting diastolic blood pressure (msDBP) X95 and o110 mm Hg and serum creatinine between X1.3 and o3.0 mg per 100 ml in males or between X1.2 and o3.0 mg per 100 ml in females were eligible. Patients began therapy with a once-daily morning oral dose of 75 mg of aliskiren. In patients with in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…In this study, aliskiren may have decreased biomarkers for CVD by improving intracellular signaling and vascular endothelial function by decreasing inflammatory mediators but not by increasing natriuresis in addition to a BP-lowering effect because all enrolled patients had oliguria or anuria. Further studies will need to investigate the mechanism of cardiovascular protective effects by aliskiren in HDD-CKD patients with hypertension Several studies reported that mean trough plasma aliskiren concentrations increased by renal impairment; 25,26 however, an increase in exposure does not correlate with the severity of renal impairment. 25 Moreover, renal clearance of aliskiren represents only a small fraction (0.1-1.0%).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, aliskiren may have decreased biomarkers for CVD by improving intracellular signaling and vascular endothelial function by decreasing inflammatory mediators but not by increasing natriuresis in addition to a BP-lowering effect because all enrolled patients had oliguria or anuria. Further studies will need to investigate the mechanism of cardiovascular protective effects by aliskiren in HDD-CKD patients with hypertension Several studies reported that mean trough plasma aliskiren concentrations increased by renal impairment; 25,26 however, an increase in exposure does not correlate with the severity of renal impairment. 25 Moreover, renal clearance of aliskiren represents only a small fraction (0.1-1.0%).…”
Section: Discussionmentioning
confidence: 99%
“…1 Aliskiren, a direct renin blocker, was released in Japan in recent years, and the drug's safety and hypotensive effects have already been reported. 2,3 However, there are still few reports in Japan on the drug's effects on diabetic nephropathy. Although reports have already been released overseas on aliskiren's renal protection effects when used in combination with ACEIs and/or ARBs, 1,4 as well as its effects against eGFR, 5 there are very few such reports on Japanese patients.…”
mentioning
confidence: 99%
“…Differences in BP between the groups were small by the end of the study period; SBP was 2 mmHg and DBP was 1 mmHg lower in the aliskiren group [22]. Ito et al [23] reported that in Japanese hypertensive patients with renal dysfunction (serum creatinine: 1.3-3.0 mg/dL in males, 1.2-3.0 mg/dL in females) treated with aliskiren (75-300 mg once daily), the mean reduction of BP from baseline to week 8 endpoint was 13.9 ±16.6 and 11.6±9.7 (mean ± S.E.M.) mmHg for SBP and DBP, respectively.…”
Section: Pharmacology Of Aliskirenmentioning
confidence: 99%
“…mmHg for SBP and DBP, respectively. Additionally, 65% patients achieved blood pressure response (mean DBP < 90 or a 10 mmHg decrease, or mean SBP < 140 or a 20 mmHg decrease), and 30% achieved blood pressure control (mean SBP < 140 mmHg and mean DBP < 90mmHg) at the week 8 endpoint [23]. Persson et al [24] examined the antiproteinuric effect of increasing doses of aliskiren (up to 600 mg) in hypertensive patients with diabetic nephropathy (eGFR: 85 mL/min/1.73 m 2 ).…”
Section: Pharmacology Of Aliskirenmentioning
confidence: 99%